Lies & illusions [videorecording (DVD)] - James, Eric; Slater, Christian; Gooding, Cuba, Jr., 1968-; Schultz, Sarah Ann (SP Releasing, 2024)
A self help author is hunted by thugs who believe the writer holds millions of dollars in diamonds stolen by his dead fiancee.